An Exploration of Teaching Style Used by Junior High School English Teacher in Teaching English - Asridawati Asridawati; Amirullah; Muhammad Tahir (International Journal of Language, Education, and Literature, 2025)
Teaching style is a crucial aspect of education because each teacher's unique approach can influence the success of the learning process. This study aimed to explore the English teacher’s implementation of teaching styles and students’ perception of these styles. A qualitative case study approach was used, with data collected through observations and interviews. Five participants were involved: one teacher and four students. The findings revealed that (1) the teacher consistently applied Grasha's five teaching styles: expert, formal authority, personal model, facilitator, and delegator. Among these, the facilitator style was most commonly used, supported by strategies like icebreaking and games to engage students and enhance motivation. (2) Students expressed positive perceptions of all teaching styles. The expert style facilitated understanding through clear explanations, while the formal authority style boosted students' confidence with constructive feedback and clear learning goals. The personal model style made it easier for students to grasp content through direct examples. The facilitator style promoted interactive learning and critical thinking with discussions and visual media. Lastly, the delegator style encouraged student independence by offering flexibility in task selection and completion time. Supporting strategies, such as games and icebreakers, helped create an enjoyable learning atmosphere, further motivating students to engage in the learning process. These findings demonstrate how diverse teaching styles contribute to creating effective and interactive learning experiences